2007
DOI: 10.1007/s10103-007-0479-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of low level laser irradiation on adult human adipose derived stem cells

Abstract: This study investigated the effect of low level laser irradiation on primary cultures of adult human adipose derived stem cells (ADSC) using a 635-nm diode laser, at 5 J/cm(2) with a power output of 50.2 mW and a power density of 5.5 mW/cm(2). Cellular morphology did not appear to change after irradiation. Using the trypan blue exclusion test, the cellular viability of irradiated cells increased by 1% at 24 h and 1.6% at 48 h but was not statistically significant. However, the increase of cellular viability as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
84
0
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(98 citation statements)
references
References 19 publications
7
84
0
7
Order By: Relevance
“…Although LLLT can increase cell proliferation if performed at early culture time, Ozawa et al [10] have shown that irradiation after 6 days of culture had no effect on cellular proliferation. In two reports, LLLT protocol was found to increase MSCs proliferation, but in both cases, cells were irradiated after one passage, which is known to reduce their innate proliferation rate [11,12]. Moreover Shimizu et al [13] reported that low-level laser effect on proliferation was mediated by the secretion of IGF-1 on rat calvaria cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although LLLT can increase cell proliferation if performed at early culture time, Ozawa et al [10] have shown that irradiation after 6 days of culture had no effect on cellular proliferation. In two reports, LLLT protocol was found to increase MSCs proliferation, but in both cases, cells were irradiated after one passage, which is known to reduce their innate proliferation rate [11,12]. Moreover Shimizu et al [13] reported that low-level laser effect on proliferation was mediated by the secretion of IGF-1 on rat calvaria cells.…”
Section: Discussionmentioning
confidence: 99%
“…Несмотря на значительный разброс энергетиче-ских параметров лазерного воздействия в исследо-ваниях по изучению влияния НИЛИ на пролифера-цию МСК, данные литературы в отношении опти-мальной ЭП для непрерывного НИЛИ с длиной волны 633-635 нм находятся в достаточно узком диапазоне -0,3-0,5 Дж/см 2 , при этом ПМ варьи-рует в значительно более широких пределах, от 3-6,61 мВт/см 2 [18][19][20][21][22][23] a -фотография клеток в проходящем свете. Ув.…”
Section: таблица 2 параметры нили-освечивания (лазерные излучающие гunclassified
“…They have also been differentiated into smooth muscle cells that are functional [27]. These cells have also shown increased viability and proliferation when exposed to LILI alone [5] and, as well as, in combination with epidermal growth factor (EGF) [28]. Recent studies have demonstrated the functional neural differentiation of human ADSCs [29].…”
Section: Adipose Derived Stem Cellsmentioning
confidence: 99%
“…Results have shown that LILI can produce negative and positive effects on stem cells. Positive results include inhibition of inflammation and increased cell viability and proliferation [4,5]. Due to ease of isolation and plasticity [6], ADSCs hold great promise for tissue engineering and regenerative medicine [7].…”
Section: Introductionmentioning
confidence: 99%